ANALISIS KETERLAMBATAN PROSES OPERASIONAL BONGKAR MUAT BATU BARA PADA KEGIATAN TRANSSHIPMENT PERUSAHAAN JASA BONGKAR MUAT - Abdillah Ma’rifatul Hakim; Suaibatul Aslamiyah (MANAJEMEN DEWANTARA, 2026)
The purpose of this study is to identify and analyze the factors causing delays in the loading, unloading, and delivery of coal during transshipment activities at PT Varia Usaha Dharma Segara and their impact on the company's operational efficiency.The research method used is a descriptive qualitative approach with the research location at PT Varia Usaha Dharma Segara. Data collection was conducted through direct observation of coal loading, unloading, and shipping activities, in-depth interviews with informants directly involved in transshipment operations according to the research criteria, and documentation of company operational data. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions based on field findings. The results of the study show that delays in coal delivery are caused by suboptimal coordination between the loading and unloading processes and the readiness of the truck fleet, inconsistent operational scheduling, and external factors such as weather conditions and field dynamics. These delays have resulted in increased waiting times, suboptimal utilization of operational resources, and decreased efficiency in the distribution process. The results of this study indicate that strengthening operational control, improving work coordination, and developing clear Standard Operating Procedures (SOPs) are strategic steps to minimize delays and improve the company's operational efficiency